Tri Kaya Parisudha Sebagai Landasan Pendidikan Moral Dan Etika Bagi Anak Muda Di Era Moderen (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2026)
Modern era has significantly influenced the mindset and behavior of the younger generation. Technological advancements and the globalization of information often lead to the erosion of moral and ethical values in daily life. In this context, the Hindu teaching of Tri Kaya Parisudha, which consists of three core principles right thinking (manacika), right speech (wacika), and right action (kayika) remains highly relevant as a foundation for character education. This research applies a qualitative approach through literature study to explore the meaning, role, challenges, and implementation of Tri Kaya Parisudha in shaping the character of Hindu youth in the modern era. The findings indicate that consistent application of Tri Kaya Parisudha values in family and school environments can serve as a practical solution to address the current moral crisis among young people. This teaching not only promotes positive behavior but also instills spiritual awareness and social responsibility.
Keywords: Tri Kaya Parisudha, youth character, moral education, modern, Hindu values